Integrasi Nilai Kepemimpinan Autentik dalam Praktik Supervisi Akademik: Strategi Menuju Sekolah Bermutu di SDN 50 Cendana - Hasanah, Uhwah; Ampry, Evy Segarawati; A.M, Muh. Inayah; Harpiani, St; Anas, Munawir Anas; Resa, Asmirinda; Hasbahuddin; Mithhar; Waqif, Abdul; Aslam (Universitas Sulawesi Barat, 2025)
This study aims to describe the integration of authentic leadership values into academic supervision practices and how this integration becomes a strategy in realizing a quality school at SDN 50 Cendana, Enrekang Regency. The approach used is descriptive qualitative, with data collection techniques through in-depth interviews, direct observation, and documentation. The results show that the principal has integrated authentic leadership values such as self-awareness, relational transparency, balanced information processing, and an internalized moral perspective in academic supervision practices. The integration of these values has a positive impact on teacher motivation, a conducive work climate, improved learning quality, and the formation of a supportive and reflective school culture. These findings indicate that authentic leadership-based academic supervision can be an effective strategy in improving the quality of education sustainably.